Kinematics of the Normal Knee during Dynamic Activities: A Synthesis of Data from Intracortical Pins and Biplane Imaging. (11th April 2017) - Gasparutto, Xavier; Moissenet, Florent; Lafon, Yoann; Chèze, Laurence; Dumas, Raphaël
Abstract : Few studies have provided in vivo tibiofemoral kinematics of the normal knee during dynamic weight-bearing activities. Indeed, gold standard measurement methods (i.e., intracortical pins and biplane imaging) raise ethical and experimental issues. Moreover, the conventions used for the processing of the kinematics show large inconsistencies. This study aims at synthesising the tibiofemoral kinematics measured with gold standard measurement methods. Published kinematic data were transformed in the standard recommended by the International Society of Biomechanics (ISB), and a clustering method was applied to investigate whether the couplings between the degrees of freedom (DoFs) are consistent among the different activities and measurement methods. The synthesised couplings between the DoFs during knee flexion (from 4° of extension to −61° of flexion) included abduction (up to −10°); internal rotation (up to 15°); and medial (up to 10 mm), anterior (up to 25 mm), and proximal (up to 28 mm) displacements. These synthesised couplings appeared mainly partitioned into two clusters that featured all the dynamic weight-bearing activities and all the measurement methods. Thus, the effect of the dynamic activities on the couplings between the tibiofemoral DoFs appeared to be limited. The synthesised data might be used as a reference of normal in vivo knee kinematics for prosthetic and orthotic design and for knee biomechanical model development and validation.